(untitled) (Biological Sciences - PJSIR, 2022)
In this study, cotton sliver characteristics were compared among different speeds of extra roller fixed under takerin and a high speed conventional card. Modified card with extra roller running at 150 rpm in clockwise motion produced dominating results over all other settings in respect to card and drawing sliver characteristics. Moreover, maximum waste extraction with minimum card web neps were also achieved at this speed.